The effect of gamification and narrative on learner engagement and academic achievement in primary schools: a South African case study - Shelton, James Duncan (Department of Computer Science, 2020)
As the major aims of primary school education are to foster both learning and enjoyment of learning, the main goal of this research project is to identify whether the use of storytelling can improve gamification of learning through a Learning Management System (LMS). Gamification is a known method for enhancing the enjoyment of learning as well asthe reinforcement of learning, in tasks that are typically seen as routine or mundane. The study used a sample of grade 7 learners from a South African private school, using the national curriculum policy document as a content guideline. The study used comparative groups of two gamified learning management systems, with one system using the storyline of “Mission to Mars”, where learners embarked on a fictional journey to Marsin search of habitable land. The other group used a similar learning management system, using generic images and discourse without using a narrative. Using game mechanics, which are common features used to structure games, the content was presented as a progression-based game to achieve the end goal of colonising Mars. Progression was based on learner participation in core activities that were required by the core curriculum and which were formally assessed, in temporal activities that occurred at different stages in time and in discretionary activities that were optional and were known not to be formally assessed. We found that the gamified systems were successful in reinforcing learning and were enjoyed by both experimental groups. It was anticipated that the use of a narrative, in conjunction with the gamified learning management system, would yield higher academic results and be more enjoyable, which was in line with research on the use of storytelling in education. Contradictory data was found, which suggests that the use of narrative should be carefully implemented, as storytelling may only be effective if presented to learners in a meaningful and relevant way. The system was developed using a free web page designer, provided by Google, which would have limited the possibilities for developing interactive or customised teaching resources for the facilitator to use. This was found to be the main limitation for the study and should influence further research in this field.